In-situ development of metal organic frameworks assisted ZnMgAl layered triple hydroxide 2D/2D hybrid as an efficient photocatalyst for organic dye degradation. (May 2021) - Bhuvaneswari, K.; Palanisamy, G.; Pazhanivel, T.; Maiyalagan, T.; Shanmugam, P.; Grace, Andrews Nirmala
Abstract: Metal organic framework (MOF) supported layered triple hydroxide (LTH) 2D/2D hybrid material was prepared by a simple hydrothermal method. The photophysical properties of the prepared samples were investigated through a set of analytical methods such as X-ray diffraction, Fourier-transform infrared spectroscopy, field emission scanning electron microscope, high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy and mapping. The photocatalytic degradation activity of as prepared 2D/2D MOF-5/LTH hybrid sample was investigated against methylene blue (MB) dye under the UV–visible light irradiation. The degradation efficiency of the MOF-5/LTH hybrid sample was twice a time greater than that of pristine MOF-5, particularly degradation efficiency of the MOF-5, LTH and MOF-5/LTH hybrid samples are 43.3, 57.7 and 98.1% respectively. The Pseudo first order rate and the reusing investigation was further used to study the catalytic activity and stability of the as-synthesized 2D/2D photocatalyst. The observed improvement in the photocatalytic activity of the hybrid samples were owed to enhance visible light absorption, efficient separation and transportation of photoinduced electrons and holes. Graphical abstract: Image 1 Highlights: The 2D/2D visible light active photocatalysis was prepared by hydrothermal method. The photocatalytic activity of MOF-5/LTH hybrid was investigated against MB dye. MOF-5/LTH hybrid shows better catalytic activity under visible light irradiation. The better degradation activity was due to the effective separation of e − and h + . Enhanced photocatalytic activity of 2D/2D (MOF-5/LTH) hybrid was revealed.